Phosphorus in soil and soybean growth as affected by phosphate fertilization and cover crop residues - Corrêa, Juliano Corulli; Mauad, Munir; Rosolem, Ciro Antônio (Pesquisa Agropecuaria Brasileira, 2004)
The efficiency of phosphate fertilizers can be affected by phosphate sources, soil properties, way of application and plant species. The objective of this work was to evaluate the effect of phosphorus levels and cover crops residues on phosphorus dynamics in the soil and soybean initial growth. The experiment was carried out in a greenhouse in pots containing a dystrophic Red Latosol (Typic Hapludox). The treatments consisted of three cover crop residues: pear millet (Penisetum americanum L.), oats (Avena strigosa) and guinea sorghum (Sorghum bicolor) at 8 t ha-1, interacting with 0, 50, 100 and 150 kg ha-1 of P , applied over straw mulch, as simple superphosphate. Phosphorus levels and the different residues affected P transport through the soil. Pear millet was more efficient in leaching available P while oats and guinea sorghum were more effective in leaching organic phosphorus.